Political Will and the Limits of Adherence to International Law in Protecting Human Rights within Prisons: Toward the Absolute Criminalization of Torture - Nasier Abd Al Hassan, Lect. Dr. Ali (Basra studies journal, 2026)
This study examines the role of political will and the limits of adherence to international law in protecting human rights within prisons, with a particular emphasis on the absolute criminalization of torture under international instruments, including the Universal Declaration of Human Rights and the Convention against Torture. The research highlights practical challenges, such as the lack of effective oversight and the prevalence of security-oriented cultures, and proposes measures to strengthen monitoring mechanisms and harmonize domestic legislation with international standards. The primary objective is to ensure comprehensive protection of prisoners’ rights and the absolute prohibition of torture through enhanced accountability and capacity-building for prison staff.